Fabrication and characterization of a refractive index sensor based on SPR in an etched plastic optical fiber - Al-Qazwini, Yusser A. Taqi; Muhammad Noor, Ahmad Shukri; Yaacob, Mohd. Hanif; Harun, Sulaiman Wadi; Mahdi, Mohd Adzir (Elsevier, 2015)
The paper presents a refractive index sensor based on surface plasmon resonance (SPR) in etched plastic optical fibers (POF). The etching approach adopted here ensures the geometrical circular symmetry of the optical fiber. The influence of design parameters namely, residual fiber thickness and sensing length on the sensitivity of the proposed sensor was investigated. A lower value of residual fiber thickness and shorter sensing length result in greater sensitivity of the sensor. The proposed sensor provides numerous advantages such as simplicity in design, low cost of fabrication, higher mechanical strength, and ease of handling compared to other SPR structures.